Exploring Students’ online Self-Regulated Learning on writing skill at Pesantren Education - Imam nur Aziz (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study focuses on using an online SRL strategy to improve the writing skills of pesantren students. SRL strategy is used for learners to set a goal, plan, and integrate their learning independently. Data are collected from 131 university students of pesantren for 16 (sixteen) weeks. Two groups: experimental and control are the same duration, but only the experimental group receives the intervention. All groups get pre-and posttest writing as well as the SRL questionnaire. The findings demonstrate that when learners use SRL in writing skills on metacognitive, social behavior, and motivational control tactics, they are more engaged and driven. Furthermore, the SRL method can raise the level of linguistics.